2020
DOI: 10.4314/ahs.v20i4.56
|View full text |Cite
|
Sign up to set email alerts
|

The impact of menopause on sexual function in women and their spouses

Abstract: Background: The purpose of this study is to evaluate the impact of menopause on sexual function in women and their spouses. Methods: This is a cross-sectional study that was conducted from January 2018 to May 2019 in Rasht (North of Iran). The participants included 215 menopausal women and their spouses. Data were collected using the demographic questionnaire, the Female Sexual Function Index (FSFI) questionnaire, and the International Index of Erectile Function (IIEF) question- naire. Results: On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Those with sexual dysfunction also reported higher rates of anxiety and depression. The impact of menopause on sexual function in women (Khalesi et al, 2020) Cross-sectional Iran Out of 215 participants, 78 women (36.28%) reported female sexual dysfunction (FSD) and 37 men (17.2%) reported erectile dysfunction (ED). Among the men who reported ED, 18 (8.37%) had mild ED, 12 (5.58%) had mild to | 6 moderate ED, and 7 (3.25%) had moderate ED.…”
Section: Resultsmentioning
confidence: 99%
“…Those with sexual dysfunction also reported higher rates of anxiety and depression. The impact of menopause on sexual function in women (Khalesi et al, 2020) Cross-sectional Iran Out of 215 participants, 78 women (36.28%) reported female sexual dysfunction (FSD) and 37 men (17.2%) reported erectile dysfunction (ED). Among the men who reported ED, 18 (8.37%) had mild ED, 12 (5.58%) had mild to | 6 moderate ED, and 7 (3.25%) had moderate ED.…”
Section: Resultsmentioning
confidence: 99%
“…Pérez‐Herrezuelo et al in Spain, 34 and in Iran, Safaei et al 32 and Jamili et al 35 showed that almost three quarters, almost three quarters, and more than three quarters of menopausal women had sexual dysfunction, respectively. However, Khalesi et al in Iran, showed that almost more than a third of their participants had female sexual dysfunction 36 . Sexual health is influenced by personal factors, interpersonal relationships, social and family traditions, culture, and religion 37 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Khalesi et al in Iran, showed that almost more than a third of their participants had female sexual dysfunction. 36 Sexual health is influenced by personal factors, interpersonal relationships, social and family traditions, culture, and religion. 37 Therefore, the reasons for the difference between this study and the present study are differences in personal factors, interpersonal relationships, and social and family traditions.…”
Section: Discussionmentioning
confidence: 99%
“…Na menopausa haverá o declínio do estrogênio, causando diversas consequências como a dispareunia que é a dor na relação sexual, causadas pela secura vaginal, diminuição da elasticidade tecidual e a atrofia urogenital que podem afetar a vida sexual das mulheres. (Khalesi et al, 2020) De acordo com o estudo realizado por Alves et al, (2016), ao avançar da idade, principalmente no período da menopausa, a prevalência de incontinência urinária (IU) é de aproximadamente 30% a 50%. Essa disfunção, apesar de não apresentar graves riscos à saúde física, pode gerar consequências psicológicas para a mulher, levando ao isolamento, sentimento de angústia e vergonha, baixa autoestima e perda da qualidade de vida.…”
Section: Qualidade De Vida De Mulheres Climatéricasunclassified